Analisis Kedudukan Mahkamah Konstitusi dalam Melaksanakan Hak Uji Materiil (Judicial Review) pada Putusan Nomor 90/PUU-XXI/2023 - Sekar Arum Kusuma Jati; Sunny Ummul Firdaus; Jadmiko Anom Husodo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The amendment of the 1945 Constitution of the Republic of Indonesia brought significant changes to the structure of state institutions, particularly in the separation of powers. The Constitutional Court, as an institution holding judicial power, has the authority to conduct judicial review based on Article 24 paragraph (2) of the 1945 Constitution. The Constitutional Court Decision No. 90/PUU-XXI/2023 sparked polemics because it was considered a positive legislative decision, which shifted the Court's role from negative legislator to positive legislator. This has created a new phenomenon in the Indonesian constitutional law system, especially regarding the position of the Constitutional Court and the validity of the constitution. This research aims to analyze the effect of the decision on the state institutional system in lawmaking. Using a normative legal approach, this research finds that the decision shows the weakness of the checks and balances system and legalizes a new norm regarding the age of presidential and vice-presidential candidates that does not reflect the interests of society. As a result, the expected substantive justice is not achieved, loosening democracy, and undermining the authority of lawmaking institutions. Therefore, it is necessary to review the authority of the Constitutional Court to prevent abuse of power.